Telaah Konsep I’jaz al-Qur'an dan Tantangannya di Era Digital - Rouf, Abdul (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2024)
This study aims to analyze the factors that influence parental involvement in children's education, using Epstein's parental involvement theory and other supporting theories. This study uses a qualitative method with a descriptive approach. The subjects of the study were parents of students in various socio-economic and cultural contexts, while the objects of the study included social, economic, cultural factors, role perceptions, educational policies, and community support. Data were collected through interviews, observations, and documentation studies, then analyzed using thematic analysis techniques. The results of the study indicate that parental involvement is influenced by social networks, economic status, cultural values, gender norms, access to technology, and educational policies. Families with strong social and economic access tend to be more involved, while families with limitations face various barriers. School and community support, as well as positive perceptions of the role of parents, have also been shown to increase involvement. This study emphasizes the importance of a holistic approach involving various stakeholders to create a supportive educational environment